2014
DOI: 10.1002/elps.201300562
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic characterization and antimicrobial activity of folk medicinal plant extracts for their applications in olive production

Abstract: Phytophthora spp is important in plant pathology due to the importance of the diseases it causes. In olive trees, severe damages are caused by the disease known as "dry branch" occasioned by Phytophthora nicotianae, P. citrophthora and P. palmivora. Much effort has been made to find efficient methods of control, with a low negative impact on environment. In this regard, treatment with plant extracts is a valid strategy. The aims of the present study are (i) to determine the polyphenol composition of extracts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Polyphenol composition of four different plant extracts from Thymus vulgaris , Origanum vulgare , Matricaria recutita , and Larrea divaricate was studied in order to correlate their composition with the inhibition of the disease and to determine the antimicrobial capacity of each individual phenolic compound against Phytophthora spp . . Thus, a SPE followed by a CZE method using 30 mM boric acid buffer at pH 9.50 was applied to all extracts.…”
Section: Phenols and Polyphenolsmentioning
confidence: 99%
“…Polyphenol composition of four different plant extracts from Thymus vulgaris , Origanum vulgare , Matricaria recutita , and Larrea divaricate was studied in order to correlate their composition with the inhibition of the disease and to determine the antimicrobial capacity of each individual phenolic compound against Phytophthora spp . . Thus, a SPE followed by a CZE method using 30 mM boric acid buffer at pH 9.50 was applied to all extracts.…”
Section: Phenols and Polyphenolsmentioning
confidence: 99%
“…Şanli and Lunte determined flavonoids including API in Chamomile and Linden extracts with the use of capillary zone electrophoresis [ 12 ]. Boiteux et al studied antimicrobial activity of plant extracts of chamomile, oregano, thyme, and creosote bush [ 13 ]. Honegr et al used large-volume sample stacking with polarity switching for determination of natural polyphenols in Orthosiphon stamineus Benth [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above, L. divaricata extract represents a great alternative for the in vitro control of P. palmivora. Noteworthy is that the antimicrobial activity of L. divaricata extract has been related with the presence of phenolic compounds (3). In this study, piperine was the only alkaloid found in the extract by HPLC-MWD analysis.…”
Section: Alkaloid Antimicrobial Activity By Solid Agar Bioassaymentioning
confidence: 63%